Standardizing Generalist Definitions to Improve Evidence in General Medicine: Addressing Diverse Interpretations and Lack of Consistency - Hirata R; Tago M; Shikino K; Watari T; Takahashi H; Sasaki Y; Shimizu T (International Journal of General Medicine, 2024)
Risa Hirata,1 Masaki Tago,1 Kiyoshi Shikino,2,3 Takashi Watari,4 Hiromizu Takahashi,5 Yosuke Sasaki,6 Taro Shimizu7 1Department of General Medicine, Saga University Hospital, Saga, Japan; 2Department of General Medicine, Chiba University Hospital, Chiba, Japan; 3Department of Community-Oriented Medical Education, Chiba University Graduate School of Medicine, Chiba, Japan; 4Integrated Clinical Education Center, Kyoto University Hospital, Kyoto, Japan; 5Department of General Medicine, Faculty of Medicine, Juntendo University, Tokyo, Japan; 6Department of General Medicine and Emergency Care, Toho University School of Medicine, Tokyo, Japan; 7Department of Diagnostic and Generalist Medicine, Dokkyo Medical University, Tochigi, JapanCorrespondence: Masaki Tago, Department of General Medicine, Saga University Hospital, 5-1-1 Nabeshima, Saga, 849-8501, Japan, Tel +81 952 34 3238, Fax +81 952 34 2029, Email tagomas@cc.saga-u.ac.jpPurpose: There has been growing interest in generalists in Japan in recent years. However, due to the diverse use of the term “generalist”, the specific roles of these physicians remain ambiguous. Consequently, the target population for research on generalists is unclear, making it challenging to conduct studies within the generalist practice framework. Therefore, a literature search was conducted to examine how generalists are defined and classified in research worldwide.Methods: We conducted a literature search that focused exclusively on articles written in English and used keywords related to generalists, general medicine (GM), primary care, and family medicine. Based on the results, six physicians working in GM reviewed the findings and discussed the identified issues and their potential solutions.Results: The definition of generalists in studies targeting GM, family medicine, and primary care conducted worldwide, including Japan, varies. Generalists exhibit diverse roles even within university hospitals in Japan. No studies provide a precise categorization or definition of generalists based on specific medical practices or roles, except for hospitalists, who are primarily involved in inpatient management in the United States.Conclusion: The definition of GM was unclear based on the results of the literature search, and the lack of uniformity in backgrounds has rendered the target population unclear. Consequently, in healthcare settings where medical systems vary by country or region, evidence from studies targeting generalists cannot readily apply to actual practice. Clarifying generalists through an explicit definition based on clinical practice will allow for a more precise target population for research on generalists and enable the accumulation of evidence related to well-defined groups of generalists, contributing to the advancement of GM. Therefore, future research is required to develop new indicators to precisely classify and define generalists.Keywords: generalist, general medicine, definition, hospitalist